Towards sustainable pharmacy practice: Community pharmacists’ experiences with medicine waste, reuse and disposal - Kingston Rajiah; Ellen McLaughlin (PLoS ONE, 2026)
Objective To explore the perspectives and experiences of community pharmacists in Northern Ireland regarding returned medicines, pharmaceutical waste, and safe disposal practices, with a focus on identifying barriers, opportunities, and policy implications. Methods A qualitative study using semi-structured in-depth interviews was conducted with 15 community pharmacists recruited through purposive sampling. Interviews were held online using Zoom or Microsoft Teams, lasting 30–45 minutes each. Data was audio-recorded, transcribed verbatim, and analysed using Braun and Clarke’s six-step inductive thematic analysis framework. Two researchers independently coded the data, and discrepancies were resolved through discussion. Results Seven key themes were identified: (1) Equitable access to return services, highlighting variability in public awareness and participation; (2) Safe pharmacy disposal practices, reflecting structured yet resource-dependent protocols; (3) Waste reduction through supply control, where pharmacists actively worked to minimise unnecessary dispensing; (4) Collaborative waste management, revealing informal partnerships with GPs and care homes; (5) Financial/Operational Burden of Disposal Services, showing frustration at the destruction of potentially reusable medications; (6) Workforce skills and support, noting a lack of formal training and clear guidance; and (7) Legal Tensions in Medicine Reuse, capturing the stiffness between waste reduction and strict safety regulations. Conclusion Community pharmacists in Northern Ireland are committed to reducing medicine waste and ensuring safe disposal, but face regulatory, operational, and workforce-related barriers. Addressing these challenges will require standardised protocols, pharmacist-led public education, and greater integration into prescribing processes. These actions directly support global efforts toward achieving the United Nations Sustainable Development Goals, including Good Health and Well-being, Responsible Consumption and Production, and Climate Action. Empowering pharmacists through training, policy support, and interprofessional collaboration is essential for building a more sustainable, equitable, and environmentally responsible healthcare system.